Desarrollo de un modelo institucional de auto-evaluación en una institución de educación superior en Colombia caso de estudio: Escuela Colombiana de Ingeniería Julio Garavito (2017)
The quality in higher education is seen in the Quality Assurance Systems (SAC), through self-assessment processes, which for a Higher Education Institution (IES), is a process of active participation of stakeholders in the identification of the strengths and weaknesses of the institution and programs, aimed at fulfilling its mission and continuous improvement. This research addresses quality management from engineering through Schnarch's Product Development methodology, whose phases contributed to the development of an institutional self-evaluation model for the Julio Garavito Colombian Engineering School, in accordance with the requirements of the National Accreditation Council , of the Ministry of National Education and the requirements of the NTC-ISO 9001: 2015. The first phase shows the needs analysis through systems dynamics (causal diagram) that describes the behavior of the stakeholders. The second, a benchmarking for the analysis of the state of the art on the implementation of the NTC-ISO 9001: 2015 in the SAC, a list of the institutions with institutional accreditation and / or certification of NTC-ISO 9001: 2015, the matrix of correlation of the self-assessment models and the requirements of the NTC-ISO 9001: 2015. The third, the generation of the concept of the model. The research work shows the results of the needs analysis and benchmarking for the development of the model. This study concludes with the construction of the integral self-assessment model that, in addition to the accreditation and qualified registration, allows IES to be certified in NTC-ISO 9001: 2015.